Predictive factors of malunion and nonunion at the Aristide le Dantec hospital - Fode I. Keita; Pape A. Diouf; Youssef Benadada; Alioune B. Dione; Badara Dembele; Charles B. Dieme (International Journal of Research in Orthopaedics, 2023)
Background: Malunion and nonunion are late complications that can occur during the fracture healing process. The aim of this study was to determine the predictive factors for malunion and nonunion Methods: This was a retrospective study over a period of 43 months. Predictive factors were sought from patient, fracture and initial management data Results: We recorded 72 consolidation disorders in 69 patients. malunion accounted for 54.1% and nonunion for 45.9%. The study population was divided as follows: 53 men and 16 women. The average age was 37.8 years. The patients lived in urban areas in 81.2% of cases. Comorbidities were present in 14.5%. The circumstances of fracture occurrence were dominated by traffic accidents, especially for 39 patients. The initial fracture was closed in 91.3%. Long bones were involved in 97.2% of cases, with a diaphyseal location in 52.8%. The fracture was simple in 79.1%, with 84.7% of the fractures being transverse. The tibia was the bone most affected by malunion (53.8%). Nonunion occurred in the humerus, femur and tibia in 27.3% each. Initial treatment was undertaken in 91.3% of patients. Conclusions: Malunion and nonunion are a reality in our daily practice. These consolidation problems occur in young patients who are victims of road traffic accidents. Diaphyseal fractures of long bones with a transverse line have been the most frequently incriminated. conservative treatment and traditional practice have favoured the development of these complications.